2017
DOI: 10.1007/s00268-017-4277-z
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Surgical Strategy for the Dissection of the Recurrent Laryngeal Nerve Using Continuous Intraoperative Nerve Monitoring

Abstract: Background The aim of this study was to describe first experiences and changes in management using continuous intraoperative neuromonitoring (C-IONM) in thyroid and parathyroid surgery. Method Retrospective analysis of patients who underwent surgery with C-IONM since 2012. Surgical maneuvers were modified when electrophysiologic events occurred. Patients with persistent loss of signal (LOS) underwent postoperative laryngoscopy. Results One hundred and one patients (of 1586 neck surgeries) were included and 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
1
34
1
2
Order By: Relevance
“…Even though in contrast with our title statement, Chávez et al's report and other recent studies have shown that CIONM is associated with significant less permanent recurrent laryngeal nerve (RLN) injuries compared to intermitted neural monitoring (IONM) [1][2][3][4][5].…”
contrasting
confidence: 75%
See 1 more Smart Citation
“…Even though in contrast with our title statement, Chávez et al's report and other recent studies have shown that CIONM is associated with significant less permanent recurrent laryngeal nerve (RLN) injuries compared to intermitted neural monitoring (IONM) [1][2][3][4][5].…”
contrasting
confidence: 75%
“…CIONM represents a gradually surgical progress, achieving and advancing to the objective of less RLN injuries [1][2][3][4][5].…”
mentioning
confidence: 99%
“…This methodological advantage makes LAR‐C‐IONM attractive for minimally invasive approaches, both endoscopic and open, in addition to alternative surgical approaches to neck endocrine surgery, such as transoral and transaxillary. Additionally, LAR‐C‐IONM is a safe technique that eliminates the need for manipulation of the vagus nerve and avoids the possibility of vagal electrode displacement intraoperatively, which disrupts the core analysis of the Automatic Periodic Stimulation system for detecting significant CMAP decrements …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LAR-C-IONM is a safe technique that eliminates the need for manipulation of the vagus nerve and avoids the possibility of vagal electrode displacement intraoperatively, which disrupts the core analysis of the Automatic Periodic Stimulation system for detecting significant CMAP decrements. 10,11,17,18 Although LAR is still an evolving technique, our experience is that it is exquisitely sensitive to changes in efferent neuron excitability induced by RLN stretch or compression. This sensitivity necessitates frequent intraoperative relaxation of retracted tissues in some patients to assess for reversibility of observed LAR-C-IONM amplitude decrements because traction injuries are reversible when prompt corrective measures are applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation